Temporal changes in ruminal microbiota composition and diversity in dairy cows supplemented with a lactobacilli-based DFM - Campbell, Bronwyn E.; Hassan, Mohammad Mahmudul; Moore, Robert J.; Olchowy, Timothy; Soust, Martin; Al Jassim, Rafat; Alawneh, John I. (Frontiers in Veterinary Science, 2025)
IntroductionThis study aimed to evaluate the impact of lactobacilli-based direct-fed microbial (DFM) supplementation on the composition and diversity of the ruminal microbiota in dairy cows. Understanding how DFM influences microbial populations can inform strategies to enhance animal health and productivity.MethodsOver a 16-month period (September 2021 to January 2023), ruminal fluid samples were collected from fifty dairy cows assigned to either a DFM-supplemented group (DFM; n = 25) or an unsupplemented control group (CON; n = 25). Microbial DNA was extracted and subjected to 16S rRNA gene amplification and sequencing. Microbial diversity was assessed using alpha- and beta-diversity metrics (p < 0.05), and linear discriminant analysis effect size (LEfSe) was employed to identify differentially abundant taxa. Multivariable analyses were used to explore associations with age, average milk production, days in milk (DIM), time, and supplementation.ResultsThe dominant bacterial phyla identified were Bacillota and Bacteroidota, while Methanobacteriaceae was the predominant archaeal family. The DFM group showed significantly higher abundance of genera such as Eubacterium_Q, Atopobium sp. UBA7741, and Sharpea (p < 0.05). Conversely, Bacillus_P_294101 and SFMI01 were more abundant in the CON group. Temporal changes in microbial composition were observed, with significant differences in community diversity and structure between groups over time.DiscussionThese findings demonstrate that lactobacilli-based DFM supplementation can significantly alter the ruminal microbial ecosystem in dairy cows. The observed microbial shifts, including increases in beneficial bacterial taxa, highlight the potential of DFM as a nutritional strategy to modulate rumen function and improve dairy cow performance.